The Analysis Of Surgical Treatment Modalities Applied For Upper Urinary Tract Stone Diseases In The State Hospital of Mus, Urology Clinic - Karaköse, Ayhan; Yüksel, Mehmet Bilgehan; Çiloğlu, Murat; Altok, Muammer (Fırat University, 2012)
Objective: In this study, the surgical approaches that were applied for the upper urinary tract stones in The State Hospital of Mus Urology Clinic, were investigated. Materials and Methods: 1108 patients who underwent surgery for upper urinary tract stones in The State Hospital of Mus Urology Clinic between February 2008 and February 2011 were retrospectively reviewed. Patients who were referred to ESWL treatment were excluded from the study. Results: The mean age was 43.7 ( 19-72 ) years. 472 patients (42.6%) were women and 636 of the sample (57.4%) were male. Endoscopic surgery was applied to 1071 (96.7%) patients [URS was performed to 962 (89.8%) patients, PCNL was performed to 109 (10.2%) patients,], and open surgery was performed to 37 (3.3%) patients [ureterolithotomy was performed to 11 (29,7%) patients, pyelolithotomy was performed to 24 (64.9%) patients and nephrolithotomy was performed to 2 (5.4%) patients]. Conclusion: In our clinic endoscopic surgery (URS for ureteral stones, PCNL for kidney stones) is preferred as the primary treatment modality for the treatment of upper urinary tract stone disease. Open surgery is rarely preferred only in selected cases.

Amaç: Bu çalışmada Muş Devlet Hastanesi üroloji kliniğinin üst üriner sistem taşlarına uyguladığı cerrahi girişimler incelenmiştir. Gereç ve Yöntem: Muş Devlet Hastanesi üroloji kliniğinde Şubat 2008 ile Şubat 2011 yılları arasında üst üriner sistem taşları için cerrahi girişim uygulanan 1108 hasta retrospektif olarak incelendi. ESWL tedavisine sevk edilen hastalar çalışma dışında bırakıldı. Bulgular: Kliniğimizde taş cerrahisi uygulanan 1108 hastanın yaş ortalaması 43,7 (19-72) dir. Bu hastaların 472'si (%42,6) kadın, 636'sı (%57,4) erkektir. Toplam 1071 (%96,7) hastaya endoskopik cerrahi [962 (%89,8) hastaya URS, 109 (%10,2) hastaya PCNL] , 37 (%3,3) hastaya ise açık cerrahi [11 (%29,7) hastaya üreterolitotomi, 24 (%64,9) hastaya piyelolitotomi, 2 (%5,4) hastaya nefrolitotomi] uygulanmıştır. Sonuç: Kliniğimiz üst üriner sistem taşlarında öncelikli olarak endoskopik cerrahiyi (üreter taşlarında URS, böbrek taşlarında PCNL) tercih etmektedir. Açık cerrahi kliniğimizde sadece seçilmiş nadir vakalarda tercih edilmektedir.
Muş Devlet Hastanesi Üroloji Kliniğinde Üst Üriner Sistem Taşı Cerrahi Girişimlerinin Analizi